Synthesis and fabrication of novel cuttlefish (Sepia officinalis) backbone biografts for biomedical applications - Aksakal, Bunyamin; Demirel, Mehtap (ELSEVIER SCI LTD, 2015)
New biografts were fabricated via the sol gel method by using different proportions of cuttlefish (Sepia officinalis) backbone and hydroxyapatite powder (HAp). The effect of the different proportions of cuttlefish (CF) on the morphology, mechanical properties and microstructure of the micro and nano scale-HAp were studied. Chemical properties and phase transformations of the fabricated biografts were characterized by SEM, XRD and FTIR analysis. Mechanical properties of the produced grafts were examined by hardness and compression tests. The results showed that crystallinity of the grafts increased with the increasing CF proportions. No significant difference was detected in its strength by changing the particle size of HAp e.g. micro and nano scale-HAp with different proportions of CF backbone. However, porosity and sinterability of the fabricated grafts were noted to increase and cracks on the surface decreased with increasing the CF backbone amount. Also, micro scale-HAp based biografts produced a higher hardness than the nano scale-HAp based biografts. The highest hardness was obtained from the biograft samples containing 40% micro scale-Hap. (C) 2014 Elsevier Ltd and Tecluia Group S.r.l. All rights reserved.
Keywords: Bone graft; Hydroxyapatite; Cuttlefish backbone; CALCIUM; BONE; ADDITIVES; SCAFFOLDS; BEHAVIOR; Materials Science